Integrating computer-mediated communication strategy instruction. Issue 2 (17th February 2016) - McNeil, Levi
Abstract : Communication strategies (CSs) play important roles in resolving problematic second language interaction and facilitating language learning. While studies in face-to-face contexts demonstrate the benefits of communication strategy instruction (CSI), there have been few attempts to integrate computer-mediated communication and CSI. The study reported in this article examined the relationship between computer-mediated CSI and CS use and types. It also investigated student perceptions of this form of instruction. Two groups of students enrolled in the same undergraduate course at a university in South Korea participated in the study. Over the course of one semester, the Strategy Group ( n = 11) participated in CSI, whereas the Comparison Group ( n = 14) did not. Throughout the semester, students in both groups completed nine chatting tasks, and transcripts from these sessions were analyzed to identify the frequency and types of CSs employed. In addition to questionnaire data showing that the Strategy Group perceived CSI favorably, the results show that the Strategy Group used significantly more CSs than the Comparison Group, and that the two groups differed in regards to specific strategies they employed. This study offers recommendations for future research investigating CS use and the instructional components of CSI.